2014
DOI: 10.1634/theoncologist.2014-0170
|View full text |Cite
|
Sign up to set email alerts
|

Management of Elderly Patients With Gliomas

Abstract: The current progressive aging of the population is resulting in a continuous increase in the incidence of gliomas in elderly people, especially the most frequent subtype, glioblastoma (GBM). This sociohealth shift, known as the "silver tsunami," has prompted the neuro-oncology community to investigate the role of specific antitumor treatments, such as surgery, radiotherapy, chemotherapy, and other targeted therapies, for these traditionally undertreated patients. Advanced age, a widely recognized poor prognost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 97 publications
2
19
0
1
Order By: Relevance
“…A possible reason may be due to the different ethnic populations they investigated. Another important reason may relate to the different age groups, as multiple lines of evidence have demonstrated that the incidence of glioma consistently rises among elderly people with the current progressive aging of the population [42,43]. These reports seem to indicate that common NER gene polymorphisms predispose to cancer possibly in an age-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason may be due to the different ethnic populations they investigated. Another important reason may relate to the different age groups, as multiple lines of evidence have demonstrated that the incidence of glioma consistently rises among elderly people with the current progressive aging of the population [42,43]. These reports seem to indicate that common NER gene polymorphisms predispose to cancer possibly in an age-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…2 Surely, other causes for these differences are related to comorbid diseases, to intolerance to medications, and to a low physiologic reserve. [20][21][22][23][24][25][26][27][28][29] When analyzing the current evidence in the treatment of GB in the elderly, we can conclude that surgery has a key role in the treatment, increasing the quality of life (QOL) and the survival rate, and that a maximal and function preserving surgery is feasible and safe, not adding many risks. The factors which predict worse postoperative results are a low KS score, chronic pulmonary disease, large tumors (> 4 cm), and previous neurological deficits.…”
Section: Discussionmentioning
confidence: 99%
“…The factors which predict worse postoperative results are a low KS score, chronic pulmonary disease, large tumors (> 4 cm), and previous neurological deficits. [20][21][22][23][24][25][26][27][28][29] Subsequently, RT is also important after surgery, with a positive influence in survival and in symptom control. [10][11][12][13][14][15][16][17][18][19] Hypofractionated radiotherapy is the preferred option to treat elderly patients, warranting the same results with higher adhesion and comfort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, glioblastoma multiforme (GBM) is the most aggressive tumor type (WHO grade 4) with dismal prognoses despite advances in various aspects of its clinical management [4]. Since therapeutic strategies for the various grades are not identical [5], distinguishing the different grades of diffuse gliomas is a critical issue in clinical settings. Determining the tumor grade relies on different pathological features including mitotic activity, cytological atypia, neoangiogenesis, and tumor necrosis.…”
Section: Introductionmentioning
confidence: 99%